If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4b + -8(4b + -3) = -2 + -2b Reorder the terms: 4b + -8(-3 + 4b) = -2 + -2b 4b + (-3 * -8 + 4b * -8) = -2 + -2b 4b + (24 + -32b) = -2 + -2b Reorder the terms: 24 + 4b + -32b = -2 + -2b Combine like terms: 4b + -32b = -28b 24 + -28b = -2 + -2b Solving 24 + -28b = -2 + -2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '2b' to each side of the equation. 24 + -28b + 2b = -2 + -2b + 2b Combine like terms: -28b + 2b = -26b 24 + -26b = -2 + -2b + 2b Combine like terms: -2b + 2b = 0 24 + -26b = -2 + 0 24 + -26b = -2 Add '-24' to each side of the equation. 24 + -24 + -26b = -2 + -24 Combine like terms: 24 + -24 = 0 0 + -26b = -2 + -24 -26b = -2 + -24 Combine like terms: -2 + -24 = -26 -26b = -26 Divide each side by '-26'. b = 1 Simplifying b = 1
| 4n-23=-8+7n | | 5(7x-8)-4x=-6x-3 | | 3z-12=12+7z | | 34-8x=2x-8(-2+2x) | | 40-8n=-8(1+4n) | | =s^3+4s^2+6 | | 8+5(6-3p)=-16-6p | | 6(-3x+1)-5x=-39-8x | | 10(3x+1+2)=34 | | 2*1r=4 | | 2x^2-40x-144=0 | | 6(5+x)-4x=24+5x | | 36-3m=-5(2m-3) | | -2n-8(-3n+4)=40+4n | | -n+3=-7(n+3) | | Tnr=pv | | 5x+3x+2x=3x+1 | | ax-c=borx | | 22+r=-(6-8r) | | 1-10y=27-3y+6 | | 5x-100+2x-25=75 | | 2x(3+y)=12 | | -20+4a=8(6-8a) | | 6(3+4x)-4=158 | | -(8x+8)-5=-8-3x | | -4n-21=-(-6-n)-2 | | 4x^2+3x+0=0 | | 81y^2-8=13 | | -32+5a=-8(a+6)+3 | | 3a-2a-a+11= | | .2x+3=8.6 | | 0=-3x^2+9x+9 |